Same-day edit and personalization of the Catholic Wedding ritual in Nueva Ecija - Gutierrez, Guia Marie Basco; Claudio, Ma Ivy A. (Quezon City College of Mass Communication, University of the Philippines, 2023)
How does a modern event documentation represent a traditional ritual? In this research, I examined how the same-day edit represents the wedding ritual. Specifically, this study looked into the mediatization of Catholic wedding ritual in Nueva Ecija and how it impacts the wedding ritual. Mediatization theory and mediatized ritual guided this research as it focused on the Catholic wedding ritual in Nueva Ecija and the same-day edit videos produced by Chris Camania Photography. In using qualitative textual analysis, the study described the Catholic wedding ritual in Nueva Ecija. analyzed the same-day edit videos produced by Chris Camania Photography, compared the SDE and the Catholic wedding ritual. and was able to discuss the impact of the mediatized ritual to the Catholic wedding ritual. The study found that the event documentation went beyond the Catholic ritual. Through media logic, it emphasizes some rites more than the others to be able to create a 'personalized" narrative that evokes an overall feeling of social ritual experience.
Keywords: medialization, wedding, ritual, videography, same-day edit, personalization
Paano inilalarawan ng event documentation ang isang tradisyunal na ritwal? Sinusuri sa pag-aaral na ito ang paglalarawan ng same-day edit sa ritwal ng kasal, lalong-lalo na kung paano naapektuhan ng mediatization ang Katolikong ritwal ng kasal sa Nueva Ecija. Sinagot ito ng pag-aaral sa pamamagitan ng paglalarawan ng Katolikong kasal sa Nueva Ecija, pagsisiyasat ng anim na piling SDE videos ng Chris Camania Photography, at paghahambing sa dalawang magkaibang proseso na ito upang maipakita ang epekto ng mediatized ritual sa Katolikong ritwal ng kasal. Ginamit sa pag-aaral ang mga tema at konsepto ng mediatization theory at mediatized ritual, kasama na ang mga datos na nakuha mula sa lokal na Katolikong kasal. mea piling SDE videos. upang maintindihan kung paano nangyayari ang proseso ng mediatization sa isang Katolikong kasal sa Nueva Ecija.

Gumamit ang nagsasaliksik ng qualitative approach sa pag-obserba sa anim na SDE videos na ginawa, at nakita dito na ang dalawang pangyayari—ang kasal at SDE video—ay nagbigay daan sa isa pang karanasan na hiwalay sa kanilang dalawa: ang produksyon ng same-day edit. Natuklasan sa pananaliksik ang pagkakaroon ng media logic ng SDE at ang paggamit nito dito upang makabuo ng 'personal' na naratibo na nagbibigay ng pakiramdam ng pagiging bahagi sa isang social na ritwat. Keywords: meditization, kasal, ritual, videography, same-day edit, personalization
Vita.
Thesis
Includes bibliographical references (pages 47-51) and appendices (pages 52-68).
Keywords: Video recording -- Philippines; Video recordings -- Production and direction; Personalization